2003
DOI: 10.1109/jqe.2003.809325
|View full text |Cite
|
Sign up to set email alerts
|

Cu HyBrID laser kinetics: optimization of HBr partial pressure and buffer-gas flow rate

Abstract: A detailed investigation into the dependence of the densities of the principal plasma species in the laser discharge on the buffer-gas operating parameters is reported. Simple expressions for the densities of the Cu, Br, and H species are derived by considering their major mechanisms for production and loss. These predict that the atomic Cu and Br densities are proportional to the HBr mass flow rate, whereas the density of H species (i.e., H and H 2) is proportional to the added HBr partial pressure. The theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Using Eq. 29 In another study on CuBr laser with HBr and H 2 additives, it was concluded that the optimal conditions of gas mixtures are necessary for improving the laser performance. Based on this estimation and using Eq.…”
Section: Effect Of the Distilled Hbr Gas On Cu-hbrl Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Using Eq. 29 In another study on CuBr laser with HBr and H 2 additives, it was concluded that the optimal conditions of gas mixtures are necessary for improving the laser performance. Based on this estimation and using Eq.…”
Section: Effect Of the Distilled Hbr Gas On Cu-hbrl Performancementioning
confidence: 99%
“…Based on this estimation and using Eq. 29 In the case of undistilled HBr gas, the injected gas components consist of HBr molecules and their dissociation products, i.e., H 2 and Br 2 . Figure 4(a) and 4(b) shows the variation of active electrical power and discharge resistance.…”
Section: Effect Of the Distilled Hbr Gas On Cu-hbrl Performancementioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated, however, that eff icient laser operation with good spatial characteristics is obtained from KE-CVLs at simultaneously high specific input-output powers and average output powers. Because of their similar plasma composition and performance characteristics, 17 Cu HyBrID lasers and CuBr lasers with H 2 additive are also likely to generate similar performance, provided that the optimum plasma mixture can be maintained at the requisite input power levels.…”
mentioning
confidence: 99%